(untitled) (Research, Society and Development, 2020)
Introduction: Alcohol abuse is present in the family and conjugal life of many Brazilians, with the main drinker being the man. Living with alcoholics implies a breakdown in affective relationships, which can be experienced through violence and overload to women. Thus, this study aims to analyze the meaning of the memory of women living with an alcoholic partner. Method: This study is a qualitative, descriptive research, based on the Oral History of Life, carried out from April to October 2019, with five women spouses / ex spouses of alcoholics, in the interior of Bahia, Brazil. The experiences were collected through semi-structured interviews recorded and transcribed, analyzed through thematic content analysis. Results: Women’s memories produced two thematic categories, The Past: challenges in conjugal coexistence; The Present: experience of resilience and empowerment. Women perceived their partners’ alcohol dependence late, experiencing behavior changes in their partners, followed by experiences of domestic violence, resulting in impacts on their mental health. Religion was present in the moral options of life that guided women resilience and empowerment. Conclusions: It is noteworthy that women realized late that alcohol abuse contributed to their partner’s aggressive behaviors. Thus, domestic violence suffered by women produced the appearance of signs of anxiety and depression. Finally, living with an alcoholic partner provided women with not only illness, but also contributed to resilience and empowerment in decision-making.